Semiotic Analysis of Taylor Swift’s ‘Midnight Rain’ Using Peirce’s Triadic Model Signs - Yusuf, Atika Hasna Nadia; Afifuddin, Muzakki (JOM, 2024)
This article aims to unveiling the symbolic meanings within the lyrics of Taylor Swift’s ‘Midnight Rain’ through Peirce’s triadic model of representamen, object, and interpretant, with the aim of providing more insight into our understanding of the interpretation of the song “Midnight Rain” in semiotic theory. This study is a literary study since the data source is the song lyrics in the “Midnight Rain, which is considered as a piece of Poetry and presented as the symbols in the forms of nouns and noun phrases. The findings of this study show eight symbols in the song lyrics of Midnight Rain such as “wasteland”, “montage”, “midnight”, “postcard”, “window”, “the present simple” and “midnight rain”. These symbols have some interpretants such as negative and positive qualities, transformation, irony, portal and regret, progression and unhappiness, presented after analyzing and establishing the representamen and objects of these symbols. According to the analyzed symbols, the meaning of “Midnight Rain” song lyric is mostly related to the celebrity sad life of a celebrity who is trapped in a celebrity world and this sadness and the regret is expressed through the phrase “midnight rain”.